The Effectiveness Of Tutoring In Higher Education (Eurasian Journal of History, Geography and Economics, 2025)
Tutoring programs in higher education play a vital role in supporting student learning, enhancing academic performance, and promoting student success. This scientific article examines the effectiveness of tutoring in higher education, exploring the benefits, challenges, and best practices associated with tutoring programs. Through a comprehensive review of research studies and empirical evidence, this article highlights the significant impact of tutoring on student outcomes and offers insights into optimizing tutoring strategies for improved educational outcomes in higher education settings.